Pengaruh Kecenderungan Neurotik Dan Self-Efficacy Terhadap Psychological Well Being Pada Mahasiswa Psikologi - Utami, Wahyu (Journal An-Nafs: Kajian Penelitian Psikologi, 2016)
The research was to determine the effect neurotic tendencies and self-efficacy toward psychologycal well being in college students. The tendency of neurotic and self-efficacy as the independent variable and psychological well-being as the dependent variable, the subjects in the research a student amounted to 100 students which consists of 52 male students and 48 female students ranging in age from of 18 to 20 years. A purposive sampling technique is used as a method of taking the subject. Analyze data use multiple linear regression analysis and data collection make use of a scale that is Psychologycal Of Well Being Scale, Big Five Inventory (BFI) and Self Efficacy Scale (SES (BFI) Psychologycal Scale Of Well Being. The results showed neurotic trends affecting the psychological well-being (? = 0241, p = 0.006). Self Efficacy affect psychological well-being with ? = 0241, p = 0.006). Neurotic tendencies and Self Efficacy toward psychological well-being (? = 20 919, p = 0.000). The research was shows that the tendency of neurotic and Self Efficacy provide effective contribution of 30.1% toward psychological well-being